Growth and yield response of the plantain (Musa spp.) hybrid FHIA 21 to shading and rooting by Inga edulis on a Southern Cameroonian ultisol - Hauser, S. (International Society for Horticultural Science, 2010)
Plantain (Musa spp.) is highly susceptible to root nematodes (Radopholussimiles) and fungal diseases of the leaves, causing yield losses in the vicinity of 50%.‘FHIA 21’ (AAB genome) is a plantain hybrid with good tolerance to pests anddiseases, excellent palatability and a high level of acceptance by farmers. Plantainproduction in Southern Cameroon is based on slash and burn of relatively old (20–40 years) secondary forest. Forest clearing is labor and cost intensive leading to theretention of large trees, species with hard wood and those of commercial value, aswell as forest bordering directly on the plantain field. Thus, plantains may be shadedto various degrees. This trial determined the growth and yield response of ‘FHIA 21’to shade imposed by various levels of canopy cover of Inga edulis. Establishment wasunaffected by shade, with 94% of plant survival at 99 days after planting (DAP).Canopy cover was negatively correlated with growth parameters of ‘FHIA 21’plants at 99 DAP. The proportion of plants that failed to produce within 525 DAPwas lowest under the lowest level of canopy cover. Failure to produce an ediblebunch due to uprooting, breaking or premature death were unaffected by shadelevels, whereby no effect on pre- and post-flowering failure could be discerned. Theproportion of plants that produced an edible bunch and the fresh bunch yield washigher in the low canopy cover area than in high canopy cover areas. Bunch massper producing plant, although highly variable, was not significantly affected byshade level. Root mass of I. edulis was weakly, yet significantly, positively correlatedwith bunch yield. ‘FHIA 21’ developed severe symptoms of Banana streak virus afterphases of low water supply, which were more frequent at higher canopy cover levels.The hybrid appears not to be suitable for systems with high levels of shading fromretained trees.